L2 listening in a digital era: Developing and validating the mobile-assisted self-regulated listening strategy questionnaire (MSRLS-Q) - Zhou, Sihan; Xu, Jian; Thomas, Nathan (System (Linköping), 2024)
Mobile technologies have transformed L2 listening. These technologies provide learners with an abundance of materials that transcend the limitations of traditional classroom instruction. Understanding how learners engage with such materials is crucial if teachers are to facilitate students' development of self-regulated listening strategies. This study reports on the development and validation of a new instrument, the Mobile-assisted Self-Regulated Listening Strategy Questionnaire (MSRLS-Q). Informed by a social cognitive understanding of self-regulation, items were generated from existing literature and semi-structured interviews with 16 Chinese undergraduate students. The questionnaire was validated through an exploratory factor analysis with 309 Chinese undergraduate students, followed by a confirmatory factor analysis with a separate sample of 327 students. Results confirmed a 31-item, five-factor model covering students' pre-, during- and post-listening strategies: Goal setting and mobile resource planning, Cognitive and metacognitive multimedia listening, Mobile-assisted motivational control, Structuring online social space, and Listening evaluation and adaptation. Structural equation modelling revealed that four of the five factors significantly predicted students’ international orientation to use English. The results emphasize self-regulated listening as a cyclical process reflective of cognitive, motivational, and social dimensions of strategy use. Implications for research and pedagogical use of the MSRLS-Q are discussed.